2018
DOI: 10.3390/microorganisms6010016
|View full text |Cite
|
Sign up to set email alerts
|

Core Sulphate-Reducing Microorganisms in Metal-Removing Semi-Passive Biochemical Reactors and the Co-Occurrence of Methanogens

Abstract: Biochemical reactors (BCRs) based on the stimulation of sulphate-reducing microorganisms (SRM) are emerging semi-passive remediation technologies for treatment of mine-influenced water. Their successful removal of metals and sulphate has been proven at the pilot-scale, but little is known about the types of SRM that grow in these systems and whether they are diverse or restricted to particular phylogenetic or taxonomic groups. A phylogenetic study of four established pilot-scale BCRs on three different mine si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 60 publications
(87 reference statements)
2
12
0
Order By: Relevance
“…Furthermore, the long term robustness and stability of these treatment systems have to be investigated. The contribution of "omics" studies is also essential for a thorough understanding of the metabolic interactions between microorganisms and pollutants and their fluctuations for improving the design and performance of such processes over long term (Ayangbenro et al, 2018;Rezadehbashi and Baldwin, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the long term robustness and stability of these treatment systems have to be investigated. The contribution of "omics" studies is also essential for a thorough understanding of the metabolic interactions between microorganisms and pollutants and their fluctuations for improving the design and performance of such processes over long term (Ayangbenro et al, 2018;Rezadehbashi and Baldwin, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This system was able to remove As, Zn and Cd from contaminated water originating from smelter waste and seemed to be controlled by interdependent microbial and abiotic reactions. Although considerable researches have been made on the design of anaerobic bioreactors, the intrinsic biology of this complex process remains poorly understood (Neculita et al, 2007;Baldwin et al, 2015;Rezadehbashi and Baldwin, 2018).…”
Section: Biological Treatment Process Relying On Sulfate Reductionmentioning
confidence: 99%
“…The fourth isolate belongs to the phylum Bacteroidetes encompassing a large number of Gram-negative and anaerobic bacteria with a wide distribution in the environment, including soil, sediments, seawater and the digestive tract of animals. This phylum includes species of the genus Bacteroides [48] that have been identified in other sulfidogenic reactors for the treatment of AMD [6,24,45,49]. Additionally, species of the genus Bacteroides have been reported with the ability to degrade the cellulolytic material [50] and to act as intermediaries in the hydrolysis stage, in anaerobic digestion [47].…”
Section: Identification Of Bacterial Isolatesmentioning
confidence: 99%
“…Current research on passive bioreactors has focused on the study of the microbial communities involved [22,23]. Environmental factors (HRT, organic source, pH, metals, sulfates, and sulfides) have a significant impact on the composition of microbial communities, and the study of reactor microorganisms is critical for the selection of phylogenetic groups as inoculum [24]. Despite this, passive bioreactors are considered less robust than chemical systems because the characteristics of AMD are variable, and microbial communities can be particularly affected by low pH and temperatures, and toxic concentrations of metals [25], which has stimulated the development of sulfidogenic diffusion exchange systems (SDES) [6,9,26].…”
Section: Introductionmentioning
confidence: 99%
“…In another paper of this special issue, Rezadehbashi and Baldwin [ 6 ] characterised the sulfate-reducing microbial communities in a number of semi-passive pilot-scale bioreactors that are used for metal-removal from mine waters. Through pyrosequencing, they showed that methanogens coexisted with sulfate reducers and competed for available substrates.…”
mentioning
confidence: 99%